Cybersecurity Efforts To Prevent and Mitigate Phishing Email Attacks - Steven Johny Runtuwene; Michael Imanuel Kaunang; Miracle Marselino Liot; Zahwa Aidila Anggai; Zaskia Salsabilla Prameswari (Publikasi Indonesia, 2026)
Background: Phishing email attacks are among the most widely occurring and dangerous threats in modern cybersecurity. These attacks aim to deceive individuals into revealing sensitive personal information such as passwords, financial credentials, and identity data. Objective: This study examines various cybersecurity strategies to detect, prevent, and respond to phishing attacks through an extensive literature review. Methods: As phishing methods evolve through social engineering, domain spoofing, malicious hyperlinks, and machine-generated deceptive messages, cybersecurity protection must adopt a layered and adaptive approach. Results: The findings indicate that technological defenses alone are insufficient without strong user awareness and behavioral readiness. Effective protection requires a combination of email authentication protocols such as SPF, DKIM, and DMARC, encryption technologies, intelligent spam filters, multi-factor authentication, artificial intelligence–based detection systems, digital literacy programs, and collaborative cybersecurity ecosystems involving governments, organizations, and end users. Conclusion: The overall conclusion emphasizes the importance of integrating technical measures with social and legal interventions to minimize the increasing risks of phishing attacks in the digital age.